Mapping the Mechanical Anisotropy of the Lithosphere using a 2D Wavelet Coherence, and its Applicaton to Australia - Kirby, Jon; Swain, Christopher (Elsevier, 2006)
We develop a new method for imaging the spatial variations of the anisotropy of the flexural response of the lithosphere, and apply it to recent topographic and gravity data sets over Australia. The method uses two-dimensional Morlet wavelet transforms, superposed in a strictly controlled geometry, to estimate the auto- and cross-spectra of the two data sets in a number of different directions. The resulting wavelet coherence is a function of scale, or wavelength, as well as orientation, and is inverted, at each spatial location, for the three parameters of an anisotropic, thin elastic plate model, i.e., maximum and minimum flexural rigidities and the orientation of the maximum. Extensive tests of the method on synthetic anisotropic, but uniform, data sets, show that it retrieves the amplitude and orientation of the anisotropy with useful accuracy. The results for Australia west of 143oE show a strong correlation with the shallower layers (75-175 km) of a recent model of seismic SV wave azimuthal anisotropy. The 'weak' axes (i.e., of minimum flexural rigidity) in most cases are approximately at right angles to the fast axes of the seismic anisotropy, implying that, for Precambrian Australia, they arise from the same source. This is most likely deformation resulting from the most recent episode of orogeny.